2011
DOI: 10.1097/aog.0b013e3182267f2f
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Floor Disorders 5–10 Years After Vaginal or Cesarean Childbirth

Abstract: Objective To estimate differences in pelvic floor disorders by mode of delivery. Methods We recruited 1,011 women for a longitudinal cohort study, 5-10 years after first delivery. Using hospital records, we classified each birth as: cesarean without labor, cesarean during active labor, cesarean after complete cervical dilation, spontaneous vaginal birth, or operative vaginal birth. At enrollment, stress incontinence, overactive bladder, anal incontinence, and prolapse symptoms were assessed with a validated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
201
4
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 280 publications
(220 citation statements)
references
References 26 publications
8
201
4
7
Order By: Relevance
“…33,34 This is clinically relevant, because operative vaginal deliveries are associated with increased risks of neonatal and maternal morbidity. [35][36][37] Many studies did not evaluate important neonatal and maternal outcomes, and when they did, they were measured differently, making statistical synthesis impossible. The methodologic quality of studies was also variable.…”
Section: Resultsmentioning
confidence: 99%
“…33,34 This is clinically relevant, because operative vaginal deliveries are associated with increased risks of neonatal and maternal morbidity. [35][36][37] Many studies did not evaluate important neonatal and maternal outcomes, and when they did, they were measured differently, making statistical synthesis impossible. The methodologic quality of studies was also variable.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the likelihood of OAB syndrome does not differ significantly in women who underwent VD or CD 5e10 years ago [46]. In another study, it has been emphasized that pregnancy state itself is a risk factor for OAB, and not the mode of delivery.…”
Section: Relationship Between the Mode Of Delivery And Oabmentioning
confidence: 97%
“…Cochrane reviews indicated that limited episiotomy should replace routine episiotomy [57e59]. Mediolateral episiotomy has been argued to be a risk factor for PFD, as it causes FI by damaging the anal sphincter [46]. Despite that, mediolateral episiotomy has not been found to increase the incidence of prolapse, UI, and FI, compared with the first-and second-degree spontaneous perineal lacerations and intact perineum [60].…”
Section: Routine Versus Selective Use Of Episiotomy For Pfdmentioning
confidence: 99%
“…Since a number of studies did not show a significant difference in the rate of SUI between women who underwent elective CS and those who underwent non-elective CS (during labour) [23][24][25][26], we did not analyse separately the results in women undergoing CS before or during labour. During pregnancy, the RVA was significantly wider than in the control group, while there were no significant differences between the second and third examinations after either VD or CS.…”
Section: Discussionmentioning
confidence: 99%